ABCB1 inhibition provides a novel therapeutic target to block TWIST1-induced migration in medulloblastoma. Issue 1 (28th April 2021) - Nasir, Aishah; Cardall, Alice; Othman, Ramadhan T; Nicolaou, Niovi; Lourdusamy, Anbarasu; Linke, Franziska; Onion, David; Ryzhova, Marina; Cameron, Hanna; Valente, Cara; Ritchie, Alison; Korshunov, Andrey; et al.
Abstract: Background: Therapeutic intervention in metastatic medulloblastoma is dependent on elucidating the underlying metastatic mechanism. We investigated whether an epithelial–mesenchymal transition (EMT)-like pathway could drive medulloblastoma metastasis. Methods: A 3D Basement Membrane Extract (3D-BME) model was used to investigate medulloblastoma cell migration. Cell line growth was quantified with AlamarBlue metabolic assays and the morphology assessed by time-lapse imaging. Gene expression was analyzed by qRT-PCR and protein expression by immunohistochemistry of patient tissue microarrays and mouse orthotopic xenografts. Chromatin immunoprecipitation was used to determine whether the EMT transcription factor TWIST1 bound to the promoter of the multidrug pump ABCB1 . TWIST1 was overexpressed in MED6 cells by lentiviral transduction (MED6-TWIST1). Inhibition of ABCB1 was mediated by vardenafil, and TWIST1 expression was reduced by either Harmine or shRNA. Results: Metastatic cells migrated to form large metabolically active aggregates, whereas non-tumorigenic/non-metastatic cells formed small aggregates with decreasing metabolic activity. TWIST1 expression was upregulated in the 3D-BME model. TWIST1 and ABCB1 were significantly associated with metastasis in patients ( P = .041 and P = .04, respectively). High nuclear TWIST1 expression was observed in the invasive edge of the MED1 orthotopic model, and TWIST1 knockdown in cell lines was associated with reduced cell migration ( P < .05). TWIST1 bound to the ABCB1 promoter ( P = .03) and induced cell aggregation in metastatic and TWIST1-overexpressing, non-metastatic (MED6-TWIST1) cells, which was significantly attenuated by vardenafil ( P < .05). Conclusions: In this study, we identified a TWIST1–ABCB1 signaling axis during medulloblastoma migration, which can be therapeutically targeted with the clinically approved ABCB1 inhibitor, vardenafil.